Fabrication of Copper Nanowire Films and their Incorporation into Polymer Matrices for Antibacterial and Marine Antifouling Applications. Issue 3 (23rd January 2015) - Jiang, Shan; Sreethawong, Thammanoon; Lee, Serina Siew Chen; Low, Michelle Bee Jin; Win, Khin Yin; Brzozowska, Agata Maria; Teo, Serena Lay‐Ming; Vancso, G. Julius; Jańczewski, Dominik; Han, Ming‐Yong
<x xml:space="preserve">Abstract</x> With the ban of tributyltin, copper‐based biocides are now widely used in antifouling coatings as the major active ingredients. Given the past experience of heavy‐metal accumulation in harbors with limited water exchange, there is a significant interest in developing copper materials that greatly reduce the amount of copper ions released into marine surroundings. In this paper, copper nanowires (NWs) encapsulated in polymer matrices are investigated as the means to control the release of copper ions and to achieve a long‐lasting antifouling effect. Very long CuNWs with high aspect ratio in organic solution are drop‐coated onto substrates to fabricate uniform thin films. They are then incorporated into an elastomeric polydimethylsiloxane (PDMS) matrix. A small amount of CuNWs in PDMS can inhibit barnacle cyprid settlement, while it exhibits low mortality to cyprids and nauplii present in the surrounding seawater environment. The low levels of copper released after 50 days suggest that the intersecting and interconnected CuNWs embedded in PDMS could potentially release copper ions continuously over a few years in seawater. This approach provides a novel platform to use hybrid materials as effective marine antifouling coatings, and may be applied to fouling release materials to enhance their antifouling properties.